Cerebral blood flow and metabolism in patients with silent brain infarction: occult misery perfusion in the cerebral cortex. Issue 3 (1st September 1998) - Nakane, Hiroshi; Ibayashi, Setsuro; Fujii, Kenichiro; Sadoshima, Seizo; Irie, Katsumi; Kitazono, Takanari; Fujishima, Masatoshi
Abstract : OBJECTIVES: Silent brain infarction (SBI) is of growing interest as a possible risk factor for symptomatic stroke. Although morphological characteristics of SBI have been well defined, their characteristic patterns of cerebral blood flow (CBF) and metabolism are in dispute. The purpose of this study was to elucidate CBF and metabolism in patients with SBI in relation to symptomatic stroke. METHODS: The patients underwent PET and were separated into three groups; control group (C group), with no lesions on CT (n=9, mean age 57), SBI group, with no neurological signs or history of stroke, but with ischaemic lesions on CT (n=9, mean age 63), and brain infarction group (BI group), with neurological deficits and compatible CT lesions in the area supplied by perforating arteries (n=19, mean age 56). Regional CBF, oxygen extraction fraction (OEF), cerebral metabolic rate for oxygen (CMRO2 ), and cerebral blood volume (CBV) were measured by PET. RESULTS: Mean values for CBF to the cerebral cortex and deep grey matter were lower in the SBI group (31.6 (SD 5.8) and 34.3 (SD 6.9) ml/100 g/min, respectively) and in the BI group (30.8 (SD 5.2), 33.9 (SD 5.9), respectively) than in the C group (36.0 (SD 6.6) and 43.5 (SD 9.5), respectively). Although mean CMRO2 of deep grey matter (2.36 (SD 0.52) ml/100 g/min) was significantly decreased in the SBI group compared with the C group (2.76 (SD 0.480), p<0.01), CMRO2 of the cortical area was as well preserved in the SBI patients (2.36 (SD 0.39)) as in the controls (2.48 (SD 0.32)) with a compensatory increase of mean OEF (0.45 (SD 0.06) and 0.41 (SD 0.05), respectively). CONCLUSIONS: Patients with SBI showed decreased CBF and CMRO2 in deep grey matter. On the other hand, decreased CBF with milder increased OEF, resulting in preserved CMRO2 in the cerebral cortex indicates the presence of occult misery perfusion, suggesting that patients with SBI have reduced cerebral perfusional reserves.